An Imbalance between Frequency of CD4+CD25+FOXP3+ Regulatory T Cells and CCR4+ and CCR9+ Circulating Helper T Cells Is Associated with Active Perennial Allergic Conjunctivitis. (4th December 2013) - Galicia-Carreón, J.; Santacruz, C.; Ayala-Balboa, J.; Robles-Contreras, A.; Perez-Tapia, S. M.; Garfias, Y.; Hong, E.; Jiménez-Martínez, M. C.
Abstract : Allergic conjunctivitis (AC) is one of the most common eye disorders in ophthalmology. In mice models, it has been suggested that control of allergic conjunctivitis is a delicate balance between Tregs and inflammatory migrating effector cells. Our aim was to evaluate the frequency of Tregs and the frequency of homing receptors expressing cells in peripheral blood mononuclear cells (PBMC) from patients with perennial allergic conjunctivitis (PAC). The analyses of phenotypic markers on CD4+ T cells and both soluble or intracellular cytokines were performed by flow cytometry. CD4+CD25+ cells were 15 times more frequent in PBMC from patients than HC; the vast majority of these CD4+CD25+ cells were FOXP3−, and most of CD4+ T cells were CCR4+ and CCR9+ cells. Upon allergen-stimulation, no significant changes were observed in frequency of Treg; however, an increased frequency of CD4+CCR4+CCR9+ cells, CD4+CD103+ cells and CD4+CD108+ cells with increased IL-5, IL-6, and IL-8 production was observed. These findings suggest an immune dysregulation in PAC, characterized by diminished frequency of Tregs and increased frequency of circulating activated CD4+ T cells; upon allergen-stimulation, these cells were expressing cell-surface molecules related to mucosa homing and were able to trigger an inflammatory microenvironment.